Exploring Sex-Based Differences in Concussion Knowledge, Attitudes and Resources in Young First Nations Hockey Players: A Cross-Sectional Survey from Ontario, Canada. Issue 2 (25th June 2019) - Hunt, Cindy; Michalak, Alicja; Johnston, Elaine; Macumber, Leila; Jocko, Tony; Ouchterlony, Donna
Abstract: Objective: Indigenous youth are vulnerable to concussion when playing hockey. A clear characterisation of sex differences among Indigenous youth could assist in tailoring future education programmes for prevention and management of concussion. The purpose of this study was to compare and contrast concussion knowledge, attitudes and resources in First Nations girls and boys playing recreational hockey. Method: The cross-sectional survey was conducted in partnership with a First Nations' chief, other Indigenous community leaders and a tertiary care head injury clinic. In Canada, researchers engaging with Indigenous peoples are expected to adhere to principles of Ownership, Control, Access and Possessions. The study included Indigenous boys and girls between the ages of 10 and 18 years of age. Results: More girls attending the hockey tournament participated in the study as compared to boys (girls n = 46, boys n = 29). More girls reported they had never experienced a concussion (73.9%), as compared to boys (58.6%) self-reports. Less than half of all study participants were able to identify some signs and symptoms of concussion such as vomiting/nausea, memory problems, fatigue and blurred vision and recognition of several concussion symptoms varied by sex. Conclusions: We created a unique partnership between Indigenous leaders and tertiary care clinic staff. Among Indigenous youth reasons for not reporting concussion symptoms to the coach varied by sex (although not reaching statistical significance), suggesting concussion education warrants tailoring for girls and boys.